The wellness equation: understanding health practices and behaviors of university students in Southern Philippines - Esto, Jomar B.; Francisco, Jemwell B.; Jr., Ruben L. Tagare; Janito, Cheeze R.; Martinez, Norge D.; Sumera, Eduard S.; Calixtro, Marichu A.; Java, Vinus P.; Jr., Moreno B. Java; Ambrocio, Gladys Pearl O.; Buisan, Jessa S.; Adlaon, Gauvin (International Journal of Public Health Science (IJPHS), 2026)
This study aimed to explore the health practices and behaviors of university students in the Southern Philippines, focusing on key domains such as health perception and management, nutritional practices, physical activity, sleep, cognitive function, and stress tolerance. Using a quantitative, descriptive correlation design, data were gathered from 1,086 students through a simple random sampling technique. The primary instrument used was the health practices and behaviors questionnaire, which assessed students' health behaviors across the various domains. Statistical analysis involved computing composite means to describe health practices and Spearman's rho to examine the interrelationships between these behaviors. Results indicated that students exhibited moderate health practices across most domains, with a significant positive correlation found between health behaviors in areas such as physical activity, stress tolerance, and sleep. The study highlights the interconnected nature of health behaviors and the need for integrated health promotion strategies that address multiple aspects of student well-being simultaneously. The findings suggest that universities should focus on holistic programs that foster healthier lifestyles, improving students’ overall health outcomes and academic performance. Future research should explore additional factors influencing student health behaviors, including socio-economic, environmental, and cultural influences, to create more targeted interventions.